Altered physical pain processing in different psychiatric conditions. (February 2022) - Kim, Diane J.; Mirmina, Julianne; Narine, Serah; Wachtel, Jonathan; Carbajal, Jessica M.; Fox, Helen; Cáceda, Ricardo
Highlights: Pain sensitivity for low intensity stimuli is reduced in depressed patients. Experimental pain sensitivity is reduced in patients with schizophrenia. Awareness of these abnormalities may improve quality of life, life expectancy. Abstract: Several reports indicate either increased or decreased pain sensitivity associated with psychiatric disorders. Chronic pain is highly prevalent in many of these conditions. We reviewed the literature regarding experimental pain sensitivity in patients with major depression, bipolar disorder, posttraumatic stress disorder (PTSD), generalized anxiety disorder, panic disorder, obsessive-compulsive disorder and schizophrenia. Electronic searches were performed to identify studies comparing experimental pain in patients with these conditions and controls. Across 31 depression studies, reduced pain threshold was noted except for ischemic stimuli, where increased pain tolerance and elevated sensitivity to ischemic pain was observed. A more pervasive pattern of low pain sensitivity was found across 20 schizophrenia studies. The majority of PTSD studies (n = 20) showed no significant differences compared with controls. The limited number of bipolar disorder (n = 4) and anxiety (n = 9) studies precluded identification of clear trends. Wide data variability was observed. Awareness of psychiatric patients' pain perception abnormalities is needed for active screening and addressing physical comorbidities, in order to enhance quality of life, life expectancy and mental health.